Analisis Hadis Tematik Etika Tidur dalam Enam Kitab Induk Hadis - Sahiriliyanti; Mus'idul Millah; Ahmad Farid; Yusuf Gunawan (Al-Mu'tabar, 2024)
Sleep etiquette is also called a habit, deed, behavior, human activity that is often carried out overy time you go to sleep. The purpose of this discurssion is the ethics off sleep according to hadith and madical science. The method used is a qualitative approach by appliying the hadith thematic method. The first object is bedtime ethics, bedtime ethics, and bedtime ethics which are formulated based on hadith themes. The second object is sleep ethics inn a medical/health context. The result of this study is the ethics of sleep in the hadith perspective. The discusion of this study explains that sleep ethics is very closely related to health, there are many positions that can help prevent disease. The conclsion from this study is that sleep ethics has many positive impacts on health.